Effect of activation temperature on the performance of Chitosan-based activated carbon for super-capacitor application - Sayem M.A.; Hannan M.A.; Ansari M.N.M.; Al-Shetwi A.Q.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Activated carbon; Activation analysis; Chitosan; Chlorine compounds; Cyclic voltammetry; Electric discharges; Electrochemical electrodes; Electrolytes; Energy dispersive X ray analysis; Pore size; Potassium hydroxide; Scanning electron microscopy; Supercapacitor; Voltage regulators; X ray diffraction analysis; Zinc chloride; 'current; Activation temperatures; Aqueous electrolyte; Biodegradable; Capacitor electrode; Electrochemicals; Performance; Performance characteristics; Super-capacitor; Symmetrics; Chemical activation